Faktor-faktor yang mempengaruhi ketidakpatuhan perawat terhadap standar mutu komite keperawatan di rumah sakit x - Radha Ayuningtyas; Tri Yahya Christina; Budi Kristanto; Risa Setia Ismandani (THE JOURNAL OF Nursing Management Issues, 2026)
Background: The quality of nursing services in hospitals is influenced by nurses’ compliance in implementing nursing quality standards developed and evaluated by the Nursing Committee. However, non-compliance among nurses with the implementation of these standards is still found at Hospital X. Purpose: To identify factors associated with nurses’ non-compliance with the Nursing Committee’s quality standards. Methods: This qualitative descriptive study involved 24 staff nurses who had participated in nursing quality standard audits and met the inclusion criteria. Participants were selected using purposive sampling. Data were collected through semi-structured interviews that were recorded, transcribed verbatim, and analyzed using Elo and Kyngäs’ inductive content analysis method. Data credibility was maintained through participant validation and in-depth data presentation. Results: One main problem topic was identified, namely nurses’ limited understanding of the Nursing Committee’s quality standards. Seven themes related to the implementation of nursing care were identified, including limited socialization, repeated documentation of vital signs, high work mobility, patient workload, non-nursing tasks, differences in educational backgrounds, limited understanding of the 3S concept and assessment process, and evaluation barriers. Regarding Standard Operating Procedures (SOPs), six themes were identified: unsustainable socialization, limited facilities, high workload, work habits, patient characteristics, and the need for continuous training. Conclusion: Nurses’ non-compliance is influenced by individual and system factors. Strengthening socialization, providing continuous training, and improving management support are needed to enhance compliance with the Nursing Committee’s quality standards Keywords: Factors; Non-compliance; Nurses; Standards; Quality Pendahuluan: Mutu pelayanan keperawatan di rumah sakit dipengaruhi oleh kepatuhan perawat dalam menerapkan standar mutu keperawatan yang dikembangkan dan dievaluasi oleh Komite Keperawatan. Namun, di Rumah Sakit X masih ditemukan ketidakpatuhan perawat terhadap penerapan standar tersebut. Tujuan: Mengidentifikasi faktor-faktor yang berkaitan dengan ketidakpatuhan perawat terhadap standar mutu Komite Keperawatan. Metode: Penelitian kualitatif dengan metode deskriptif terhadap 24 perawat pelaksana yang telah mengikuti audit standar mutu komite keperawatan dan memenuhi kriteria inklusi. Partisipan dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui wawancara semi- terstruktur yang direkam, ditranskripsikan secara verbatim, dan dianalisis menggunakan analisis isi induktif metode Elo dan Kyngas. Keabsahan data dijaga melalui validasi partisipan dan penyajian data secara mendalam. Hasil: Ditemukan satu topik permasalahan utama, yaitu rendahnya pemahaman perawat terhadap standar mutu komite keperawatan. Terdapat tujuh tema terkait pelaksanaan asuhan keperawatan, meliputi sosialisasi terbatas, pengulangan dokumentasi tanda vital, mobilitas kerja tinggi, beban pasien, tugas non-keperawatan, perbedaan latar belakang pendidikan, keterbatasan pemahaman konsep 3S dan pengkajian, serta kendala evaluasi. Pada aspek SPO, ditemukan enam tema, yaitu sosialisasi yang belum berkelanjutan, keterbatasan sarana, beban kerja tinggi, kebiasaan kerja, karakteristik pasien, dan kebutuhan pelatihan berkelanjutan. Simpulan: Ketidakpatuhan perawat dipengaruhi oleh faktor individu dan sistem. Diperlukan penguatan sosialisasi, pelatihan berkelanjutan, serta dukungan manajemen untuk meningkatkan kepatuhan terhadap standar mutu komite keperawatan. Kata Kunci: Faktor, Ketidakpatuhan, Perawat, Standar, Mutu.